2019
DOI: 10.1063/1.5092530
|View full text |Cite
|
Sign up to set email alerts
|

Measure synchronization and clustering in a coupled-pendulum system suspended from a common beam

Abstract: In this paper, we investigate measure synchronization (MS) in a nondissipative coupled-pendulum system suspended from a common beam. The system consists of several identical pendula hanging from a common beam that are indirectly coupled through the movements of the beam. We find that as the ratio R of the mass of the common beam to the mass of each pendulum decreases, which, in turn, increases the coupling strength between the pendula, the coupled-pendulum can achieve MS, including partial MS and complete MS, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…This feature is shared by measure synchronization in two coupled classical Hamiltonian system, where two subsystems get frequency-locked with very few frequencies being involved. [19] In contrast, for quantum measure synchronization, we have found that the frequency locking involves multiple frequencies.…”
Section: Measure Synchronizationmentioning
confidence: 95%
See 2 more Smart Citations
“…This feature is shared by measure synchronization in two coupled classical Hamiltonian system, where two subsystems get frequency-locked with very few frequencies being involved. [19] In contrast, for quantum measure synchronization, we have found that the frequency locking involves multiple frequencies.…”
Section: Measure Synchronizationmentioning
confidence: 95%
“…[9] Being identical, the only difference in between the coupled Hamiltonian systems are their initial conditions. [9,[15][16][17][18][19][20] Even though for coupled quantum Hamiltonian and classical Hamiltonian systems, Ĥa and H b , the two Hamiltonian systems are intrinsic different. Here we shall relax the requirement by setting the classical Hamiltonian system and quantum Hamiltonian system in exact correspondence except for their initial conditions.…”
Section: Measure Synchronizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the geometry is simple, this problem involves abundant flow physics, including vortex shedding, resonance, harmonics and synchronisation. The present problem setup is also relevant to the Huygens' pendulum of two synchronised oscillators (Huygens, 1660;Peña Ramirez et al, 2014;Tian et al, 2019) and the interacting tuning forks (Klein et al, 2012).…”
Section: Introductionmentioning
confidence: 99%